Dynamic aggregation method for wind farms for overvoltage protection and accuracy stability enhancement - Zongzheng Wang; Chenlei Liu; Wei Wang; Tong Zhao; Yifan Liu; Zhijuan Wang; Ying Sun; Xiaolong Wang (International Journal of Electrical Power & Energy Systems)
Existing equivalent methods for permanent-magnet synchronous generator (PMSG) wind farms struggle to precisely simulate dynamic characteristics during overvoltage faults and protection triggering, thereby limiting their applicability in transient stability analysis under extreme grid conditions. This paper proposes a novel dynamic aggregation method that integrates overvoltage protection mechanisms. First, the paper analyzes the operational boundaries of grid-side converters (GSC) during high voltage ride through (HVRT) and overvoltage protection states, proposing a maximum reactive power constraint model to capture dynamic reactive power behavior during overvoltage protection triggering. Further investigation quantifies the relationship between wind turbine’s maximum reactive power and wind speed under extreme operational limits, developing a wind-speed-dependent reactive power model. In the study of aggregation methods, it was found that the choice of aggregation parameters for the overvoltage protection phase directly affects the aggregation accuracy. We developed a dynamic aggregation method that prioritizes maximum reactive power equivalence over wind speed homogeneity, effectively decoupling aggregation errors from wind farm dispersion patterns. Simulation results from a offshore wind farm system confirm the method’s superior performance compared to traditional high voltage ride through approaches, maintaining enhanced accuracy during overvoltage faults and consistent stability across diverse wind distribution scenarios. This methodology provides a robust solution for electromagnetic transient simulations requiring precise representation of protection-triggered dynamics in offshore wind farms.